2018
DOI: 10.1371/journal.pone.0206757
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of mRNA-miRNAs related to intramuscular fat content in the longissimus dorsi in Xinjiang brown cattle

Abstract: In this study, we examined the role of mRNAs and miRNAs in variations in intramuscular fat content in the longissimus dorsi muscle in Xinjiang brown cattle. Two groups of Xinjiang brown cattle with extremely different intramuscular fat content in the longissimus dorsi were selected for combined of miRNA and mRNA analysis using an RNA-Seq. In total, 296 mRNAs and 362 miRNAs were significantly differentially expressed, including 155 newly predicted miRNAs, 275 significantly upregulated genes, 252 significantly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…These milk and meat type cattle were selected by this hybridization to resist cold and rough handling and to exhibit flexibility and adaptability to livestock farming [ 6 ]. Li et al [ 7 ] constructed a network of differentially expressed mRNAs and microRNAs (miRNAs) based on their expression in the longissimus dorsi muscle of Xinjiang brown cattle. Our previous research have found 46 differentially expressed circular RNAs and 346 differentially expressed miRNAs in longissimus dorsi samples from Kazakh cattle and Xinjiang brown cattle [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These milk and meat type cattle were selected by this hybridization to resist cold and rough handling and to exhibit flexibility and adaptability to livestock farming [ 6 ]. Li et al [ 7 ] constructed a network of differentially expressed mRNAs and microRNAs (miRNAs) based on their expression in the longissimus dorsi muscle of Xinjiang brown cattle. Our previous research have found 46 differentially expressed circular RNAs and 346 differentially expressed miRNAs in longissimus dorsi samples from Kazakh cattle and Xinjiang brown cattle [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xinjiang Brown Cattle is an excellent new breed of grass-fed livestock that has independent intellectual property rights and is bred in China. Xinjiang brown cattle breeding and improvement, meat type breeding and other traditional cross-breeding programs have done much work and played an important role in the cattle industry [7][8][9]. However, the taste and flavor of Xinjiang brown beef severelyseriously restrict the development of the Xinjiang brown cattle industry [10].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, all the variants in mRNA can affect stability due to the mRNA secondary structure and free energy [ 30 , 31 ]. However, the functional mechanisms underlying the associations are largely unknown [ 32 , 33 , 34 ]. To more clearly and comprehensively reveal the complex connections between the four haplotypes and miR-184, luciferase assay was performed to investigate the influence of the functional SNP loci.…”
Section: Discussionmentioning
confidence: 99%